Table of Content - - (Arab Journal for Sciences and Research Publishing, 2024)
Table of Content: 1. The Use of Generative Artificial Intelligence in Graduate Studies Research: A Case Study Mr. Turki Mohammed Habkoor Almoharraq 2. The problem of complexity and Consistency in the intelligence cycle: A critique of the effects of structural and dynamic interactions on intelligence efficiency Dr. Mohamed Elzin Mohamed Ahmed Ibrahim 3. Evaluation of the Governance of the National Initiative for Human Development and Its Impact on Territorial Development in Morocco’s Eastern Rif from 2005 to 2024: A Case Study of the Oulad Zbair and Beni Frassen Communities Mr. Mohamed El-Fazziki, Ms. Fatima Ghmimed, Dr. Jawad El-Bazwi, Dr. Abdelouahed Bouberria 4. The Big Five factors of personality model: A study of history, evolution, and areas of application in the digital context Dr. Reda El-Yazidi 5. Draft proposal to facilitate the receipt and kissing of black stone for pilgrims and worshipers Dr. Mohamed Hanafy Abdullah Morsy 6. Economic relations between The Extremity Maghreb and Western Sudan during The Eighth Century AH, Fourteenth century AD. Dr. Assadik Ahmad Adam., Dr. Mahamat Saleh Daway